Staying Ahead of the Digital Technological Curve Using Survey Methods (Quality Advancement in Nursing Education - Avancées en formation infirmière, 2020)
In the early 20th century, surveys were an innovative and neoteric methodology. Collected in person or by mail, researchers could ascertain the thoughts and opinions of a small sample, which could then be applied to the general population. Almost 100 years later, the use of surveys has become pervasive in society due to digital technological advancement. However, while the digital evolution has not only altered the possibilities of how, when, and where surveys may be administered, the threats to this methodology has also evolved. While issues related to previously known errors (e.g., sampling error, non-response error) remain and have also evolved, new threats regarding confidentiality and privacy, design issues, and others, have emerged in response to this digital advancement. Novice and experienced researchers alike should be cognizant of the impact digital technologies have had on survey data collection to ensure high quality research findings. This paper explores the threats to survey methodology due to digital technological changes and discusses how novice researchers and students can mitigate these challenges.